2016
DOI: 10.1371/journal.pone.0152053
|View full text |Cite
|
Sign up to set email alerts
|

The Nanomechanical Properties of Lactococcus lactis Pili Are Conditioned by the Polymerized Backbone Pilin

Abstract: Pili produced by Lactococcus lactis subsp. lactis are putative linear structures consisting of repetitive subunits of the major pilin PilB that forms the backbone, pilin PilA situated at the distal end of the pilus, and an anchoring pilin PilC that tethers the pilus to the peptidoglycan. We determined the nanomechanical properties of pili using optical-tweezers force spectroscopy. Single pili were exposed to optical forces that yielded force-versus-extension spectra fitted using the Worm-Like Chain model. Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…Atomic force microscopy (AFM) was first developed in 1986 [ 34 ] and relies on the control of the force acting between a sharp tip, usually made of silicon nitride, and the surface while scanning a sample ( Figure 1 a). Especially in microbiology, its high-resolution imaging capacities have attracted many scientists who have used this technology to image the structure and ultrastructure of various types of bacterial cells [ 33 , 35 , 36 , 37 ].…”
Section: Sensitive Force Probes and Their Use For Single Molecule mentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic force microscopy (AFM) was first developed in 1986 [ 34 ] and relies on the control of the force acting between a sharp tip, usually made of silicon nitride, and the surface while scanning a sample ( Figure 1 a). Especially in microbiology, its high-resolution imaging capacities have attracted many scientists who have used this technology to image the structure and ultrastructure of various types of bacterial cells [ 33 , 35 , 36 , 37 ].…”
Section: Sensitive Force Probes and Their Use For Single Molecule mentioning
confidence: 99%
“…This pili structure was also proposed for pili from Streptococcus pneumoniae TIGR4 [ 101 , 102 ] and further evidenced by force-measuring optical tweezers experiments [ 103 ]. Gram-positive pili, and particularly streptococcal pili (including lactococci) seem to share a common quaternary structure with a linear assembly of subunit that are not fully optimized to dissipate energy from environmental forces [ 18 , 34 , 103 ] as it is the case for E. coli pili [ 104 , 105 ]. Interestingly, pathogenic piliated E. coli strains express helix-like pili that dampen the external forces and minimize the load at the tip in interaction with a specific host receptor [ 105 , 106 , 107 , 108 ].…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, under shear flow, a more critical contribution of MUB protein than pili was found. The importance of pili was further dissected in relation with their nanomechanical properties as probed with optical tweezer ( Castelain et al, 2016a , b ). AFM blocking assays also revealed that mucin neutral oligosaccharides were involved in adhesion of L. lactis TIL448 to PGM ( Le et al, 2013 ).…”
Section: Tools To Decipher the Role Of L Lactis Smentioning
confidence: 99%
“…The cell surface itself is characterized by properties like charge and hydrophobicity (Ly et al, 2008 ), which are determined by the molecular composition of the cell wall. The cell wall consists of peptidoglycan (Chapot-Chartier and Kulakauskas, 2014 ), polysaccharides (Ruas-Madiedo et al, 2002 ), proteins, teichoic, and lipoteichoic acids, lipids (Pelletier et al, 1997 ) and can be decorated with a sugar pellicle (Chapot-Chartier et al, 2010 ), pili (Telford et al, 2006 ; Oxaran et al, 2012 ; Meyrand et al, 2013 ; Castelain et al, 2016 ), and/or an S-layer (van der Mei et al, 2003 ). The charge of the cell surface is determined by positively and negatively charged groups on teichoic and lipoteichoic acids, polysaccharides, proteins, and pili (Delcour et al, 1999 ; Boonaert and Rouxhet, 2000 ; Chapot-Chartier et al, 2010 ), while its hydrophobicity is related to the presence of polysaccharides, LPS, and (glyco-) proteinaceous material (Pelletier et al, 1997 ; Firoozmand and Rousseau, 2016 ), as well as pili (Tarazanova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%